Citrus pectin modulates chicken peripheral blood mononuclear cell proteome in vitro - G. Ávila; M. Bonnet; D. Viala; S. Dejean; G. Grilli; C. Lecchi; F. Ceciliani (Poultry Science)
ABSTRACT: Citrus pectin (CP) is a dietary fiber used in animal nutrition with anti-inflammatory properties. CP downregulates chicken immunoregulatory monocytes' functions, like chemotaxis and phagocytosis, in vitro. The molecular underlying background is still unknown. This study investigated the activity of CP on chicken peripheral blood mononuclear cells (PBMC) proteome. An overall number of 1503 proteins were identified and quantified. The supervised sparse variant partial least squares—discriminant analysis (sPLS-DA) for paired data highlighted 373 discriminant proteins between CP-treated and the control group, of which 50 proteins with the highest abundance in CP and 137 in the control group were selected for Gene Ontology (GO) analyses using ProteINSIDE. Discriminant Protein highly abundant in CP-treated cells were involved in actin cytoskeleton organization and negative regulation of cell migration.Interestingly, MARCKSL1, a chemotaxis inhibitor, was upregulated in CP-treated cells. On the contrary, CP incubation downregulated MARCKS, LGALS3, and LGALS8, which are involved in cytoskeleton rearrangements, cell migration, and phagocytosis. In conclusion, these results provide a proteomics background to the anti-inflammatory activity of CP, demonstrating that the in vitro downregulation of phagocytosis and chemotaxis is related to changes in proteins related to the cytoskeleton.